The Effectiveness of Retrofitting RC Frames with a Combination of Different Techniques - Saadi, M.; Yahiaoui, D. (Engineering, Technology & Applied Science Research, 2022)
During the last two decades, the attention of researchers has been focused on repairing and retrofitting concrete frames to make them more earthquake-resistant. Two methods have been developed to increase the seismic resistance of previously undamaged structures before they are subjected to an earthquake. The first is through the addition of new structural members, such as steel braces and the second is by selectively strengthening structural elements, for instance through steel caging. Seismic response analysis results have been utilized in multi-story RC frames that were designed without seismic design criteria. This study aims to determine whether the retrofitting technique is effective based on comparisons between steel braces, steel cages, and their combinations. The seismic performance is defined by the seismic code for Algeria RPA 2003 according to the latest recommendations. Static nonlinear analysis was used to compare seismic responses of existing non-ductile reinforced concrete RC frames under a variety of retrofit schemes. The results show that retrofitting with steel caging gives excellent performance in terms of ductility and low shear capacity. The retrofitting with steel bracing increased the shear capacity but led to a severe ductility deficiency. The retrofitting structure combined with steel bracing and steel caging shows good performance in shear capacity and ductility. Using the Zipper system (steel bracing) and V system in combination with steel caging gives similar results to the RPA model.